Fabrication and Optimization of Nanocatalyst for Biodiesel Production: An Overview - Bano, Sayfa; Ganie, Adil Shafi; Sultana, Saima; Sabir, Suhail; Khan, Mohammad Zain (Frontiers in Energy Research, 2020)
Necessity and exploitation of fossil fuel products are implacable in serving the needs of humanity despite being a finite and limited resource. To meet the thrust of energy, biofuels derived from varieties of renewable resources are imperative in fulfilling the demand of renewable fuels on a large scale without creating environmental concerns. Biofuels are inevitably the result of the carbon fixation process which stores chemical energy, ultimately reducing the total amount of carbon dioxide. Different kinds of biofuels like bioethanol, biomethanol, biogas, and biodiesel are derived depending on varieties of feedstock materials. Among these, production of biodiesel augments the progression of clean and renewable fuel. In this review, we have discussed the production of biodiesel derived from various feedstock and using several processes like pyrolysis, direct blending, micro-emulsion, and trans-esterification, with critical discussion focussing on increasing biodiesel production using nanocatalysts. Biodiesel production mainly proceeds through homogenous and heterogeneous catalysis via trans-esterification method. The review further discusses the significance of nanocatalyst in heterogeneous catalysis based trans-esterification for large scale biodiesel production. With the advent of nanotechnology, designing and modification of nanocatalyst gives rise to attractive properties such as increased surface area, high thermal stability, and enhanced catalytic activity. The role of nanocatalysts have been extensively studied and investigated in regard to the increased biodiesel production. Along with the modification of nanocatalysts, we have briefly discussed the physico-chemical properties and the role of the optimization parameters as it plays a pivotal role in enhancing the biodiesel production commercially.